Asymmetries in two-dimensional trunk and knee kinematics during a single-leg drop landing post anterior cruciate ligament reconstruction - Vorensky, M.; Peredo, D.; Colón, W.; Rao, S.; Kakar, R. S. (International Journal of Athletic Therapy & Training, 2023)
The purpose of this study was to compare interlimb asymmetries in trunk and knee kinematics during a single-leg drop landing between athletes 9 months post anterior cruciate ligament reconstruction (post-ACLR) and healthy athletes using two-dimensional analysis. Thirty-three recreational athletes (12 post-ACLR and 21 healthy) participated in the study. Participants post-ACLR showed significantly higher limb symmetry indices in peak trunk flexion (144.0%, SE drop landing kinematics: 22.7%) when compared to healthy participants (100.6%, SE: 10.5%; z = 2.17, p = .03) and lower limb symmetry indices in peak knee flexion (85.3%, SE: 3.6%) when compared to healthy participants (98.0%, SE: 3.3%; z = -2.43, p = .01). Two-dimensional analyses of a single-leg drop landing is a clinically applicable tool that can identify interlimb asymmetries in peak trunk flexion and peak knee flexion kinematics in athletes greater than 9 months post-ACLR when compared to healthy athletes.